2009
DOI: 10.4317/medoral.15.e32
|View full text |Cite
|
Sign up to set email alerts
|

Accuracy, sensitivity and specificity of fine needle aspiration biopsy in salivary gland tumours: A retrospective study

Abstract: 15 (1):e32-7. Accuracy, sensitivity and specificity of the fine needle aspiration http://www.medicinaoral.com/medoralfree01/v15i1/medoralv15i1p32.pdf AbstractObjective: The aim of this study was to evaluate the diagnostic accuracy, sensitivity and specificity of fine needle aspiration biopsies (FNAB) of salivary gland tumours performed at the Erasto Gaertner Hospital over the course of a four year period. Study design: A retrospective study was carried out between 2001-2005 to review the cases of patients with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
10

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 20 publications
2
21
0
10
Order By: Relevance
“…The overall accuracy has been reported to be 82% to 94% in distinguishing benign from malignant lesions. FNAC also has a reported sensitivity of 65% to 85% and a specificity of 90% to 100% ( [3], [4], [5], [6]). Table 2 shows that the sensitivity, specificity and accuracy of FNA diagnosis of salivary glands obtained in this study is comparable with the data obtained in similar studies done previously.…”
Section: Results and Observationsmentioning
confidence: 99%
“…The overall accuracy has been reported to be 82% to 94% in distinguishing benign from malignant lesions. FNAC also has a reported sensitivity of 65% to 85% and a specificity of 90% to 100% ( [3], [4], [5], [6]). Table 2 shows that the sensitivity, specificity and accuracy of FNA diagnosis of salivary glands obtained in this study is comparable with the data obtained in similar studies done previously.…”
Section: Results and Observationsmentioning
confidence: 99%
“…Additionally, the degree of differentiation of neoplastic cells can be determined, which may aid in the selection of the type of surgical intervention. However, in the management of salivary gland masses, the cytology results of FNAB should be interpreted along with the clinical findings and radiological investigations (2). When performed and analyzed by experienced hands, FNAB has the advantage of providing valuable diagnostic data in a relatively short period of time (6).…”
Section: Introductionmentioning
confidence: 99%
“…Salivary gland tumors account for 3-10% of head and neck tumors (1)(2)(3). Fine-needle aspiration biopsy (FNAB) of the salivary gland mass is considered as an important diagnostic tool, although some controversy exists (4,5).…”
Section: Introductionmentioning
confidence: 99%
“…In the study by Al- Khafaji et al (1998), reported the sensitivity of 82%, a specificity of 86% and an overall diagnostic accuracy of 84%. In the study by Stramandinoli et al (2010) after comparing 79 cases of result of aspiration and pathological results, the sensitivity was reported 86.2%, specificity 87.7% and the diagnostic value 82.3%, positive predictive value 86.2% and negative predictive value 87.7%.…”
Section: Discussionmentioning
confidence: 99%